Handbook of experimental existential psychology - Greenberg, Jeff, 1954-; Koole, Sander L., 1971-; Pyszczynski, Thomas A. (Guilford Press, 2004)
Social and personality psychologists traditionally have focused their attention on the most basic building blocks of human thought and behavior, while existential psychologists pursued broader, more abstract questions regarding the nature of existence and the meaning of life. This volume bridges this longstanding divide by demonstrating how rigorous experimental methods can be applied to understanding key existential concerns, including death, uncertainty, identity, meaning, morality, isolation, determinism, and freedom. Bringing together leading scholars and investigators, the Handbook presen.